Herpes Simplex Virus 2 Blepharokeratoconjunctivitis. (4th March 2022) - Yadav, Sanya; Commiskey, Patrick; Kowalski, Regis P.; Jhanji, Vishal
ABSTRACT: Purpose: To retrospectively review the clinical characteristics of patients with herpes simplex virus type 2 (HSV-2) blepharokeratoconjunctivitis. Methods: Laboratory-proven HSV-2 blepharokeratoconjunctivitis cases were reviewed between 1995 and 2021. Results: Ten of 725 (1.4%) patients had HSV-2 infection. Data were available for nine patients. Associated conditions included neonatal herpes (1/9, 11%), severe atopy (1/9, 11%), genital herpes (2/9, 22%), and systemic immune disorders (2/9, 22%). The most common presenting finding was pain and blurred vision (55.5%). Two patients (22%) had dendritic lesions and one patient (11%) had reduced corneal sensation. Complete resolution was reported in four patients (44.5%). Recurrence was noted in four patients (44.5%) despite antiviral prophylaxis. Corneal complications included scarring and neovascularization. The visual acuity at the last follow-up was 20/40 or worse in four patients (44.5%). Conclusions: HSV-2 is an uncommon cause of keratitis. Dendrites and loss of corneal sensation were uncommon. Recurrence was noted despite antiviral prophylaxis.